TOPIC CLASSIFICATION ON TWITTER USING CNN WITH WORD2VEC FEATURE EXPANSION - Bintang Ramadhan, Rifaldy; Budi Setiawan, Erwin (Informatika, Universitas Jenderal Soedirman, 2024)
Twitter is a social networking site that enables users to communicate with their followers by sending them short messages known as